2008
DOI: 10.1029/2008gl034245
|View full text |Cite
|
Sign up to set email alerts
|

Fracture propagation propensity in relation to snow slab avalanche release: Validating the Propagation Saw Test

Abstract: [1] The 'Propagation Saw Test' (PST) was designed to assess the fracture propagation propensity of weak snowpack layers in relation to snow slab avalanche release. Its predictions were tested against independent field observations of weak layer fracture initiation and slope-scale fracture propagation (e.g., avalanche release). A total of 170 tests were performed at 23 sites. Approximately 76% of tests correctly predicted the observed slope-scale fracture propagation or lack thereof; however, 20% of tests predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…In other words, the false instability ratio for the PST in our results was 0% (Table 2). Gauthier and Jamieson (2008) report a false instability ratio of 5% for the 57 tests they conducted on stable slopes. Looking at ECT results reveals that the fracture propagated across the extended column completely in three cases, for a false instability ratio of about 9% (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…In other words, the false instability ratio for the PST in our results was 0% (Table 2). Gauthier and Jamieson (2008) report a false instability ratio of 5% for the 57 tests they conducted on stable slopes. Looking at ECT results reveals that the fracture propagated across the extended column completely in three cases, for a false instability ratio of about 9% (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…Our laboratory experiments are related to failure initiation as we study the development of the initial crack needed for fracture propagation. To study fracture propagation field tests with large samples are needed, such as the propagation saw test developed by Gauthier and Jamieson [2008] and Sigrist and Schweizer [2007].…”
Section: Discussionmentioning
confidence: 99%
“…PST experiments to study propagating cracks have confirmed deformation of the slab to substantially contribute to the mechanical energy consumed by crack extension (van Herwijnen et al, 2010). Further, Gauthier and Jamieson (2008b) have shown that the critical crack length together with the fracture result are related to slope instability. In particular, cracks propagating to the end of the column after saw cut lengths less than 50 % of the column length were clear indicators of high crack propagation propensity.…”
Section: Introductionmentioning
confidence: 98%